THE EFFECT OF GOOD GOVERNANCE IMPLEMENTATION AND HUMAN RESOURCE COMPETENCE ON FRAUD PREVENTION - Zeyn, Elvira; Farhah Fadhilah Yunus, Farhah Fadhilah Yunus (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2025)
Fraud prevention in Bandung’s local government agencies remains challenging despite the implementation of good governance. Ongoing fraud cases suggest weak oversight. Although human resource competence supports effective governance, its role in fraud prevention remains insufficiently studied. This study aims at examining the influence of good governance implementation and human resource competency on fraud prevention in the OPD of Bandung City. Using a quantitative approach, the research evaluated how these factors contributed to creating a transparent, accountable, and fraud-free work environment while identifying other relevant influencing variables. The study’s findings indicated that the implementation of good governance and human resource competence played a crucial role in preventing fraud.